An Empirical Analysis of the theory of optimum currency areas for the EAEC countries (Journal of Economic Research & Business Administration, 2016)
This working paper attempt an empirical analysis of the main assumptions of the theory of optimum currency areas in relation to the problem of creating a single currency area in the territory of the Eurasian Economic Union (EAEC). There highlighted the theoretical optimum currency area criteria that defines the most significant costs and benefits of monetary integration in the territory of the EAEC. In this paper was analyzed mac roeconomic statistics that allow us to obtain a numerical estimate of the selected criteria and an analysis of conformity of individual countries EAEC with participation of Russia to existing criteria of optimal currency area. As the basis of this analysis was taken the theory of optimum currency areas the main terms of which were laid by Mundell, Kenen, McKinnon. Conclu sions and recommendations was presented regarding the attractiveness of monetary integration for different countries EAEC.
Keywords: the volatility of exchange rate; real shocks; monetary shocks; optimum currency area.